12 epic climbing adventures - Bell, Samantha (Epic adventures., 2019)
Highlights twelve climbing adventures around the world including scaling the Eiger in Switzerland, climbing the cliffs at Laem Phraueaa Nang, and hiking the Kilauea volcano. Contains a world map, color photographs, statistics, a glossary, and resources for further reading.